Train to Adulthood - Trencsényi, Klára (Hungary : Éclipse Film, 2015)
Train to Adulthood is the coming-of-age story of three Hungarian youngsters who work at the Budapest Children’s Railway. This small-gauge railway was created in 1948 for the pioneers, Hungary’s communist youth organization, and since then it has been continuously used. Hundreds of thousands of passengers a year travel along the winding tracks of the Buda Hills with the railway operated by children aged 10 to 14, who run all the stations and accompany passengers on their journey. Viktor, his sister Kármen, and Gergő are passionate about their work on the Children’s Railway. For them it is a place of comradery and a refuge from the chaos and indifference of today’s society. Their families are struggling to get by, barely making ends meet in Hungary or working abroad. In the end, Viktor and Kármen loose their home and Gergő has to choose between following his own dream or joining his parents abroad. While the children enjoy acting as responsible adults on the railway, they are forced to mature abruptly due to the difficulties at home.
Verzio Film Festival Submission
Keywords: Documentary films